A proposal to explore the role of sustainability indicators in local governance contexts: the case of Palmela, Portugal - Moreno-Pires, Sara (2019)
The actual use of sustainability indicators and their steering potential is constrained by the particularities of governance contexts, by institutional patterns and changes, by the different interpretations of what sustainable development means and entails, and by the tensions around the main values nurturing the positions of the most relevant actors. This paper proposes a normative conceptual framework to further explore the role of sustainability indicators in local governance contexts, and applies it to the Portuguese municipality of Palmela. It aims to contribute to a better understanding of how, why and in what circumstances the processes of developing and using indicators can be important steering mechanisms for governance for sustainability, particularly at the local level. The methods used include primary literature review and official documents and data, interviews to local public officers and qualitative analysis. Palmela provides insights on concrete government achievements through the implementation of sustainability indicators, but clearly shows how they are insufficient to foster innovative governance arrangements for sustainability. The normative framework enables the identification of successes and failures of developing and using sustainability indicators in improving local governance and ultimately in helping to achieve sustainability goals.